Influência de hormônios vegetais sobre a morfo-fisiologia e virulência de Cryptococcus gattii - Vanessa da Silva Dutra de Carvalho (2016)
Cryptococcus gattii is an environmental yeast, globally distributed. This yeast is one of the main causative agents of cryptococcosis, a severe systemic fungal infection whose origin is exclusively environmental. This fungus is often isolated from plants, indicating that there is between these organisms a possible association, which can be influenced by plant metabolites, such as plant hormones (HV) auxin and gibberellin. This work aimed to evaluate the in vitro influence of plant hormones on the morpho-physiology, resistance and virulence factors of C. gattii. Initially, C. gattii cells pretreated with different concentrations of gibberellic acid (gibberellin) and 3-indoleacetic acid (auxin) underwent morphometric analysis. Both auxin as gibberellin induce strain-dependent morphological changes in the capsule and the surface/volume ratio of C. gattii. After that, some strains were selected according to their profile of morphometric changes. They were used for infection of the nematode Caenorhabditis elegans to evaluate the virulence of yeast previously treated with HV, through the worm survival. Gibberellin decreased survival of the worm in three of the four strains tested. On the other hand, auxin increased survival in two of three strains tested. Furthermore, HV-treated cells were also submitted to phagocytosis assay amoebae. The yeast survival within the amoebae was lower in three of four strains treated with gibberellin and in two of three strains treated with auxin. This yeast probably adopts different strategies forward to interacting with worms and amoebas. To understand these changes in fungal response after contact with HV, tests were performed to measure the production of enzymes related to virulence factors, such as superoxide dismutase and peroxidase, and to identify the metabolic rate, zeta potential and lipid peroxidation. Auxin increased SOD and PER activity, both enzymes are related to virulence in C. gattii. These results give an insight in order to begin to understand the complexity of the interaction between C. gattii and plants and the influence of this interaction on the morpho-physiology and yeast virulence.